Does audit partner individualism reduce client earnings comparability? Evidence from the United States - Kim, Young Hoon; Li, Yinghua; Wang, Dechun (Contemporary Accounting Research, 2025)
Abstract We examine whether audit partner individualism reduces earnings comparability in the United States. We argue that individualistic audit partners are more likely to deviate from internal working rules and allow clients more flexibility in making accounting choices, consequently decreasing their clients' earnings comparability. Using a novel partner‐level measure of individualism, we find that within individual Big 4 audit firms, earnings are less comparable between a company audited by an individualistic partner and a company audited by a non‐individualistic partner, relative to a pair of companies that are each audited by a non‐individualistic partner. Our inferences are robust to a changes analysis, a falsification test, and a propensity score matching procedure. We also find that the effect of partner individualism is less salient when the audit firm is under more stringent regulatory monitoring and when clients are more important, but more salient when individualistic partners are more confident about being different. Further analyses suggest that our main inferences are robust to controlling for differences in partners' cultural backgrounds and using client‐pairs audited by the same audit partner. Collectively, our study provides novel evidence on the role of auditor individualism in earnings comparability.